2003
DOI: 10.1021/np030150y
|View full text |Cite
|
Sign up to set email alerts
|

Complex C-Glycosyl Flavonoid Phytoalexins from Cucumis sativus

Abstract: Extraction of cucumber leaf tissue expressing induced resistance against powdery mildew fungi revealed the presence of two new major C-glycosyl flavonoid products: vitexin-6-(4-hydroxy-1-ethylbenzene) (cucumerin A, 1) and isovitexin-8-(4-hydroxy-1-ethylbenzene) (cucumerin B, 2). In addition, the known C-glycosyl flavonoids apigenin-8-C-beta-D-glucopyranoside (vitexin, 3), apigenin-6-C-beta-D-glucopyranoside (isovitexin, 4), luteolin-8-C-beta-D-glucopyranoside (orientin, 5), and luteolin-6-C-beta-D-glucopyranos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(55 citation statements)
references
References 22 publications
5
50
0
Order By: Relevance
“…In particular, cereals like wheat, rice, and maize mainly accumulate C-glycosyl flavones that are involved in protection against UV-B radiation and defense against pathogens (12)(13)(14). For example, maysin, the C-glycosyl flavone predominant in silk tissues of some maize varieties, is a natural insecticide against the corn earworm Helicoverpa zea (15,16), whereas C-glycosyl flavonoids identified in cucumber leaves act as phytoalexins in defense against powdery mildew fungi (17,18). From another perspective, there is an increasing interest for C-glycosyl flavones because of their benefits for human health and their possible applications in the prevention of diverse diseases (19,20).…”
Section: Flavonoids Accumulate In Plant Vacuoles Usually As O-glycosymentioning
confidence: 99%
“…In particular, cereals like wheat, rice, and maize mainly accumulate C-glycosyl flavones that are involved in protection against UV-B radiation and defense against pathogens (12)(13)(14). For example, maysin, the C-glycosyl flavone predominant in silk tissues of some maize varieties, is a natural insecticide against the corn earworm Helicoverpa zea (15,16), whereas C-glycosyl flavonoids identified in cucumber leaves act as phytoalexins in defense against powdery mildew fungi (17,18). From another perspective, there is an increasing interest for C-glycosyl flavones because of their benefits for human health and their possible applications in the prevention of diverse diseases (19,20).…”
Section: Flavonoids Accumulate In Plant Vacuoles Usually As O-glycosymentioning
confidence: 99%
“…Within each of the major groups of secondary metabolites such as alkaloids, phenylpropanoids and terpenoids, several thousand individual compounds accumulating in plants have been characterised and their role in plant-pathogen interactions studied (Ishihara et al, 2011). For example, induction of phenolic compounds, flavonoid phytoalexins, (Daayf et al, 1997, Fawe et al, 1998, Fofana et al, 2002, McNally et al, 2003b, McNally et al, 2003 was reported in cucumber plants following pathogen attacks and elicitor treatments. Synthesis of phytoalexins involves the rapid transcriptional activation of genes encoding a number of key biosynthetic enzymes that include anthranilate synthase (AS) (IshiharaHashimotoTanaka et al, 2008) phenylalanine ammonia-lyase (PAL), chalcone synthase (CHS) which is the early committed key enzyme of the flavonoid/isoflavonoid pathway, chalcone isomerase (CHI) and isoflavone reductase (IFR) (Dixon et al, 1995, Baldridge et al, 1998, Fofana et al, 2002, Fofana et al, 2005.…”
Section: Secondary Metabolitesmentioning
confidence: 99%
“…Synthesis of phytoalexins involves the rapid transcriptional activation of genes encoding a number of key biosynthetic enzymes that include anthranilate synthase (AS) (IshiharaHashimotoTanaka et al, 2008) phenylalanine ammonia-lyase (PAL), chalcone synthase (CHS) which is the early committed key enzyme of the flavonoid/isoflavonoid pathway, chalcone isomerase (CHI) and isoflavone reductase (IFR) (Dixon et al, 1995, Baldridge et al, 1998, Fofana et al, 2002, Fofana et al, 2005. The chemical nature of some of these compounds is now well elucidated (Ibanez et al, 2010, Ishihara et al, 2011, McNally et al, 2003. McNally et al (McNally et al, 2003b, McNally et al, 2003 reported the synthesis of complex C-glycosyl flavonoid phytoalexins, referred to as vitexin-6-(4-hydroxy-1-ethylbenzene) (cucumerin A) and isovitexin-8-(4-hydroxy-1-ethylbenzene) (cucumerin B), as a site-specific response to fungal penetration in cucumber.…”
Section: Secondary Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many kinds of plant C-glycosides have been reported (Franz and Grün 1983), and the most common are the flavonoid C-glycosides that have been found in mosses, liverworts, ferns, gymnosperms, monocots, and dicots (Jay 1994;Talhi and Silva 2012). These C-glycosides are known to show various biological activities in planta, such as antioxidant, antifungal, insecticide, and allelochemical activities (Byrne et al 1996;Hooper et al 2010;Jay 1994;McNally et al 2003). In animals, flavonoid C-glycosides have shown antioxidant, antiinflammatory, antihyperglycemic, anti-obesity, and anti-ulcer activities (reviewed by Talhi and Silva 2012).…”
Section: Introductionmentioning
confidence: 99%